EMERGENCE AND DEVELOPMENT OF THE SONNET GENRE IN ENGLISH LITERATURE (Conferencea, 2022)
In this article formation and introduction of the sonnet genre in English literature is discussed. Its time and place of appearance and emergence in England is investigated. The contribution of William Shakespeare as the first English poet adopted this complex poetic form, his transformation and transferring it to future generations are revealed.